Enemies of the future? Questioning the regimes of promising in emerging science and technology. (3rd August 2021) - Robinson, Douglas K R; Audétat, Marc; Joly, Pierre-Benoit; Van Lente, Harro
Abstract: This editorial introduces the basic idea and content of the special section 'Enemies of the future? Questioning the regimes of promising in emerging science and technology'. It sheds light on how visions and stories of technological futures are being produced and, in combination, have stabilized into 'regimes of promising' that shape emerging technoscientific domains and guide research, innovation, and governance within these domains. The special section zooms in to particular illustrative instances that reveal the dynamics of the dominant regime of promising and also reveal how they are breaking down and in some cases being replaced by alternatives. The purpose of this special section is to show the importance of regimes of promising for research and innovation policy and to stimulate further discussions on alternative regimes of promising and their ramifications.